Synergistic Effects of Alkali Activator Dosage on Carbonation Resistance and Microstructural Evolution of Recycled Concrete: Insights from Fractal Analysis and Optimal Threshold Identification - Yier Huang; Aimin Gong; Zhuo Jin; Yulin Peng; Shanqing Shao; Kang Yong (Buildings)
The synergistic mechanism between alkali activation and carbonation in fly ash recycled aggregate concrete (FRAC) remains a critical challenge for enhancing durability and promoting solid waste utilization. This study systematically investigates the effects of CaO-based alkali activator dosages (0%, 4%, 8%, 12%) on carbonation resistance, compressive strength, and pore structure evolution. The results demonstrated 8% CaO maximized compressive strength (48.6 MPa, 10.76% higher than the control group) and minimized porosity (22.87% vs. 39.33% in untreated samples), with enhanced carbonation resistance (35% depth reduction after 28 days). Fractal dimension (FD) analysis revealed that 8% dosage optimized pore complexity (FD > 1.9), forming a dense C–S–H/AFt network that suppressed CO2 diffusion. CaO addition introduces embodied carbon (9.84 kg CO2/m3), and the synergy between fly ash’s cement replacement (120 kg CO2/m3 reduction) and extended service life (theoretically, 15–20 years) ensures a net carbon benefit. These findings establish 8% as a critical threshold for optimizing alkali activation efficiency and durability in low-carbon concrete design. These findings offer theoretical and technical foundations for low-carbon concrete design and sustainable solid waste recycling in construction.